MSC-Derived Extracellular Vesicles Activate Mitophagy to Alleviate Renal Ischemia/Reperfusion Injury via the miR-223-3p/NLRP3 Axis - Zejia Sun; Zihao Gao; Jiyue Wu; Xiang Zheng; Shizhao Jing; Wei Wang (Stem Cells International)
Background. MSC-derived extracellular vehicles (EVs) exhibit a protective functional role in renal ischemia/reperfusion injury (RIRI). Recent studies have revealed that mitophagy could be a potential target process in the treatment of RIRI. However, whether MSC-derived EVs are involved in the regulation of mitophagy in RIRI remains largely unknown to date. Methods. RIRI model was established in vivo in mice by subjecting them to renal ischemia/reperfusion. TCMK-1 cells were subjected to hypoxia/reoxygenation (H/R) stimulation to mimic RIRI in vitro. BMSCs and BMSC-derived EVs were isolated and identified. Renal injury was assessed using H&E staining. The qPCR and western blot analyses were conducted to detect the mRNA and protein levels. Apoptosis was evaluated using the TUNEL assay and flow cytometry analysis. The EVs, autophagosomes, and mitochondria were observed using TEM. The colocalization of autophagosomes with mitochondria was confirmed through the confocal assay. The direct binding of miR-223-3p to NLRP3 was validated through the dual-luciferase assay. Results. BMSCs and BMSC-derived EVs were successfully isolated from mice and identified. The protective effect of BMSC-derived EVs against RIRI was validated both in vitro and in vivo, which was indicated by a decrease in apoptosis and inflammasome activation and an increase in mitophagy. However, this protective effect was impaired in the miR-223-3p-depleted EVs, suggesting that miR-223-3p mediated this protective effect. Further mechanistic investigation revealed that miR-223-3p suppressed inflammasome activation to enhance mitophagy by directly targeting NLRP3. Conclusion. In conclusion, the protective role of BMSC-derived EVs and exosome-delivered miR-223-3p in RIRI was validated. Exogenous miR-223-3p directly targeted NLRP3 to attenuate inflammasome activation, thereby promoting mitophagy.